SPE Improved Oil Recovery Symposium 2010
DOI: 10.2118/129971-ms
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Viscoelastic Property Database for EOR Polymers

Abstract: Partially hydrolyzed polyacrylamide (HPAM) and related polymers are widely used as mobility control agents in all chemical EOR applications, and an accurate characterization of their apparent viscosity in the reservoir rock is crucial for design and performance evaluation of these processes. Their apparent viscosity in porous media generally decreases as flow velocity increases; however, beyond a certain critical velocity, the apparent viscosity sharply increases, showing shear-thickening behavior. A procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Storage and loss moduli decrease due to the addition of salt. 98,99 Modulus crossover point of the copolymer did not significantly change with temperature. Rashidi et al 56 evaluated the effect of the degree of sulfonation on shear stability and found that the increase in the degree of sulfonation has increased the shear stability due to increased rigidity.…”
Section: Rheology Of Am-amps Copolymermentioning
confidence: 83%
“…Storage and loss moduli decrease due to the addition of salt. 98,99 Modulus crossover point of the copolymer did not significantly change with temperature. Rashidi et al 56 evaluated the effect of the degree of sulfonation on shear stability and found that the increase in the degree of sulfonation has increased the shear stability due to increased rigidity.…”
Section: Rheology Of Am-amps Copolymermentioning
confidence: 83%
“…This model accounts for both rheological behaviors and was successfully used to history-matched data taken from published laboratory reports. Kim et al (2010) used this viscoelastic model to develop a database for HPAM polymer solutions for a wide range of polymer concentration, salinity, and hardness, and temperature making it more practical to quantify the apparent viscosity of the polymer solution at reservoir conditions. Recently, further improvement of the parameters of this model was presented by Sharma et al (2011).…”
Section: Shear Thickening Effectmentioning
confidence: 99%
“…The most sensitive polymer to brine and multivalent ions is hydrolyzed polyacrylamide. This sensitivity results in a loss of viscosity and thus increasing mobility (Kim et al, 2010). As the literature proposed, the polymer displaced by 5 wt% NaCl dyed-water has less retention on the pore walls as compared to the polymer retention of very low salinity water.…”
Section: Experiments Iii: Effect Of Salinity On Polymer Retentionmentioning
confidence: 96%